2007
DOI: 10.1002/bit.21222
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cell culture performance using inducible anti‐apoptotic genes E1B‐19K and Aven in the production of a monoclonal antibody with Chinese hamster ovary cells

Abstract: Mammalian cells are used for the production of numerous biologics including monoclonal antibodies. Unfortunately, mammalian cells can lose viability at later stages in the cell culture process. In this study, the effects of expressing the anti-apoptosis genes, E1B-19K and Aven, separately and in combination on cell growth, survival, and monoclonal antibody (MAb) production were investigated for a commercial Chinese Hamster Ovary (CHO) mammalian cell line. CHO cells were observed to undergo apoptosis following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 38 publications
3
65
1
Order By: Relevance
“…Nivitchanyong et al (2007) found that co-expression of Aven and E1B-19K enhanced BHK cell survival and cell growth and delayed apoptosis relative to the cell lines expressing E1B-19K alone. Also in agreement with our finding is the fact that co-expression of Aven with E1B-19K enhanced protection relative to the expression of either gene alone in batch and fed-batch CHO DHFR cultures (Figueroa et al, 2007). The current study extends these findings in CHO K1 by showing that the expression of two antiapoptosis genes leads to a significant reduction in caspase activity and improved mitochondrial membrane potential in the presence of insults including staurosporine and extended batch cultures.…”
Section: Expression Of Anti-apoptotic Genessupporting
confidence: 91%
“…Nivitchanyong et al (2007) found that co-expression of Aven and E1B-19K enhanced BHK cell survival and cell growth and delayed apoptosis relative to the cell lines expressing E1B-19K alone. Also in agreement with our finding is the fact that co-expression of Aven with E1B-19K enhanced protection relative to the expression of either gene alone in batch and fed-batch CHO DHFR cultures (Figueroa et al, 2007). The current study extends these findings in CHO K1 by showing that the expression of two antiapoptosis genes leads to a significant reduction in caspase activity and improved mitochondrial membrane potential in the presence of insults including staurosporine and extended batch cultures.…”
Section: Expression Of Anti-apoptotic Genessupporting
confidence: 91%
“…(Fassnacht et al 1999;Tey et al 2000;Goswami et al 1999;Simpson et al 1999;Fussenegger et al 2000;Mastrangelo et al 2000a, b;Meents et al 2002;Chiang and Sisk 2005;Kim and Lee 2002;Sung and Lee 2005;Sauerwald et al 2006;Ifandi and Al-Rubeai 2005). Viral homologues of Bcl-2 including E1B19K have also been used for the inhibition of apoptosis in mammalian cell cultures (Wong et al 2006;Figueroa et al 2006), where E1B19K inhibits the apoptotic activity of p53 (Debbas and White 1993;Lowe and Ruley 1993).…”
Section: Mirna Targets Regulating Apoptosismentioning
confidence: 99%
“…Increasing cell density by either reducing apoptosis (Meents et al 2002;Figueroa et al 2007) or altering cell metabolism (Chen et al 2001) can lead to increase in product titers. Alternatively, the protein synthesis and secretion machinery can be targeted to increase the specific productivity of a cell.…”
Section: Introductionmentioning
confidence: 99%